Improved decoding algorithm for the generalized EVENODD array code - Haibo, Jiang; Mingyu, Fan; Yilong, Xiao; Xiaojing, Wang; Yu, Wu (2012 2nd International Conference on Computer Science and Network Technology, 2012)
Data placement scheme based on the generalized EVENODD array code was one of the most important choices for data storage systems to tolerate failures. The efficiency of the erasure code was directly related to the number of XOR operations during the encoding and decoding. We provided an improved decoding algorithm of the generalized EVENODD array code for correcting various triple node failures. It showed that the decoding complexity of the new algorithm was much lower than those of the existing comparable algorithm, thus it made the generalized EVENODD array code more efficiency in storage systems.